The learning experience of Iraq middle-aged adult learner in online undergraduate degree - Saleh, Jasim Mohammed; Lafta, Ahmed Hamdan; Man, Norsida; Abdul. Latiff, Ismail; Mohd Nawi, Nolila; Salih, Suham Mahdi; Habeeb, Asaad Khamees (International Institute for Science, Technology & Education, 2015)
This paper has based an interview with an Iraq Middle-aged adult female to gain her experience at how she completed an online course in Iraq. The paper presents findings from a case study which explored insights of her experience in online English programme in Iraq. The research questions focused on why Middle-aged adult learners could carry on and complete the programme, what factors supported her completion of the programme, and which conditions seemed to slow down the process. Findings from the interviews suggest that interaction in the learning, accessibility of the programme and encouragement from others were some of the factors that facilitated the completion of the programme. However, multiple roles for female students, technology related problems and disappointment were some of the major challenges for completion of the programme.